Den Umgang mit Geld und Konsum lernen – Verbraucherbildung in der Schule - Schlegel-Matthies, Kirsten (Stimme der Familie)

Was ist Verbraucherbildung? – Was kann sie leisten? - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Ernährungssozialisation und -bildung und die Entstehung einer "kulinarischen Vernunft" - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Heindl, Ines (Die Zukunft auf dem Tisch. Analysen, Trends und Perspektiven der Ernährung von morgen)

Ernährung und Diätetik - Schlegel-Matthies, Kirsten; Methfessel, Barbara ("Gesunde Lebensführung" - kritische Analyse eines populären Konzepts)

Mahlzeit im Wandel - die Entideologisierung einer Institution - Schlegel-Matthies, Kirsten (Mahlzeiten. Alte Last oder neue Lust?)

Frühe Hilfen sind eine Zukunftsinvestition. Eine Kosten-Nutzen-Analyse im Projekt „Guter Start ins Kinderleben“ im Auftrag des Nationalen Zentrums Frühe Hilfen - Meier-Gräwe, Uta; Wagenknecht, Inga (Frühe Kindheit)

Kosten und Nutzen Früher Hilfen. Eine Kosten-Nutzen-Analyse im Projekt "Guter Start ins Kinderleben" - Meier-Gräwe, Uta; Wagenknecht, Inga (Materialien zu Frühen Hilfen)

Validation of protein intake assessed from weighed dietary records against protein estimated from 24 h urine samples in children, adolescents and young adults participating in the Dortmund Nutritional and Longitudinally Designed (DONALD) Study - Bokhof, Beate; Günther, Anke LB; Berg-Beckhoff, Gabriele; Kroke, Anja; Buyken, Anette (Public Health Nutrition)

Trends in dietary carbohydrate quality during puberty from 1988 to 2007: a cause for concern? - Cheng, Guo; Libuda, Lars; Karaolis-Danckert, Nadina; Alexy, Ute; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (British Journal of Nutrition)
The extent to which the quality of dietary carbohydrates (CHO) changes throughout puberty is not known. We analysed trends in the quantity and quality of CHO intake among German adolescents by separately examining trends during puberty (pubertal trends) and trends in CHO intake from 1988 to 2007 (secular trends). Linear mixed-effects regression analyses were performed in 216 participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed Study who had provided weighed 3 d dietary records at the onset of the pubertal growth spurt (defined by age at take-off) and over the subsequent 4 years. Over the course of puberty, CHO quality changed little: added sugar intake from beverages increased in girls (0·25 ( se 0·12) % energy (% E)/year, P = 0·04) and added sugar intake from sweets decreased in both sexes (boys: − 0·22 ( se 0·11) % E/year, P = 0·049; girls: − 0·20 ( se 0·10) % E/year, P = 0·04). For both sexes, significant upward secular trends were observed for CHO (% E), glycaemic load (g/MJ) and added sugar intakes from sources other than sweets and soft drinks (% E), while absolute fibre intake (g/d) decreased ( P ≤ 0·04). Concomitant increases in total added sugar intake (% E) and decreases in fibre and whole-grain densities (g/MJ) ( P = 0·001–0·02) were confined to boys only. The quality of dietary CHO consumed by healthy German adolescents shows notable secular declines, but does not change markedly during puberty. Public health initiatives should be tailored to improve the overall quality of CHO nutrition.

Relation of isoflavones and fiber intake in childhood to the timing of puberty - Cheng, Guo; Remer, Thomas; Prinz-Langenohl, Reinhild; Blaszkewicz, Meinolf; Degen, Gisela H; Buyken, Anette (The American Journal of Clinical Nutrition)